Morphological and functional relationships with ultrasound measured muscle thickness of the upper extremity and trunk. (November 2014) - Abe, Takashi; Loenneke, Jeremy P.; Thiebaud, Robert S.; Loftin, Mark
Unless a subject's muscle is relatively small, a single image from a standard ultrasound can only measure muscle thickness (MT). Thus, it is important to know whether MT is related to morphological and functional characteristics of individual muscles of the extremity and trunk. In this review, we summarize previously published articles in the upper extremity and trunk demonstrating the relationships between ultrasound-measured MT and muscle morphology (cross-sectional area, CSA and muscle volume, MV) and muscular or respiratory function. The linear relationship between MT and muscle CSA or MV has been observed in biceps brachii, triceps brachii, pectoralis major, psoas major, and supraspinatus muscles. Previous studies suggest that MT in the upper arm and trunk may reflect muscle CSA and MV for the individual muscles. Unfortunately, few studies exist regarding the functional relationship with ultrasound MT in the upper extremity and trunk. Future research is needed to investigate these findings further.